Macroinvertebrate assemblages in relation to environments in the dongting lake, with implications for ecological management of river‐connected lakes affected by dam construction. Issue 3 (31st October 2016) - Pan, Baozhu; Wang, Haijun; Li, Zhiwei; Ban, Xuan; Liang, Xiaomin; Wang, Hongzhu
Abstract : The Dongting Lake, a river‐connected lake, plays a vital role in people's living, agricultural production, and ecological security of the Yangtze River basin. A systematic investigation of macroinvertebrates was conducted in the Dongting Lake during May 2004 ‐ January 2005. Altogether 65 taxa belonging to 27 families and 53 genera were identified. The annual average density and biomass of total macroinvertebrates were 265 ind/m 2 and 2.40 g dry mass/m 2, respectively. It is demonstrated that seasonal variation existed in environmental factors structuring macroinvertebrate assemblages of the Dongting Lake. Hydrological parameters (i.e., flow velocity, water depth) were the driving factors for macroinvertebrate assemblages in spring and summer, whereas the concentrations of water nutrients (i.e., phytoplankton chlorophyll a, total dissolved phosphorus) played the leading role in governing macroinvertebrate assemblages in autumn and winter. After operation of the Three Gorges Dam in 2009, the Dongting Lake may be confronted with the threat of species diversity declining and assemblage structure changing. Thus, ecological restoration measures shall be put forward. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 914–920, 2017